Sputum inflammatory cell-based classification of patients with acute exacerbation of chronic obstructive pulmonary disease. - Peng Gao (Public Library of Science (PLoS), 2013)
Background Patients with chronic obstructive pulmonary disease (COPD) commonly suffer from acute exacerbations (AECOPD) and display varying disease severity. However, there is no available biomarker for the classification of AECOPD. This study is aimed at investigating the sputum cellular profiles to classify patients with AECOPD. Methods A total of 83 patients with AECOPD and 26 healthy controls were recruited. Their demographic and clinical characteristics were recorded, and their lung function was examined. The phenotypes of sputum inflammatory cells were characterised, and the concentrations of sputum and serum amyloid-A (SAA), C-reactive protein (CRP), interleukin-6 (IL-6), and matrix metalloproteinase-9 (MMP-9) were measured. Based on the sputum inflammatory cell profiles, individual patients were categorized into one of the four subgroups with inflammatory eosinophilic, neutrophilic, paucigranulocytic, and mixed granulocytic AECOPD. Most AECOPD patients were reevaluated within 12-14 months after discharge. Results There were 10 (12%) eosinophilic, 36 (43%) neutrophilic, 5 (6%) mixed granulocytic, and 32 (39%) paucigranulocytic AECOPD patients. The patients with mixed granulocytic or neutrophilic AECOPD had a higher BODE score, more sputum inflammatory cells, lower lung function, and longer hospital stay, accompanied by higher concentrations of sputum MMP-9, IL-6 and CRP, and serum SAA, IL-6 and CRP. Notably, 83% of patients with neutrophilic AECOPD displayed evidence of bacterial infection and many of them responded poorly to standard therapies. In addition, patients with mixed granulocytic or neutrophilic stable COPD remained at lower lung functions and higher levels of inflammation. Conclusion Patients with AECOPD display heterogeneous inflammation, and the profiles of sputum inflammatory cells may be used as valuable biomarkers for the classification of AECOPD patients.